2015
DOI: 10.1017/s0047279415000483
|View full text |Cite
|
Sign up to set email alerts
|

Knights and Knaves in the English Medical Profession: the Case of Clinical Excellence Awards

Abstract: We elaborate Le Grand's thesis of ‘knights and knaves’ in terms of clinical excellence awards (CEAs), the ‘financial bonuses’ which are paid to over half of all English hospital specialists and which can be as much as £75,000 (€92,000) per year in addition to an NHS (National Health Service) salary. Knights are ‘individuals who are motivated to help others for no private reward’ while knaves are ‘self-interested individuals who are motivated to help others only if by doing so they will serve their private inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It has been criticised as being elitist, and questions have been asked regarding the scheme's value for money. 14 , 15 Specific concerns have been raised 16 (and acknowledged by the Advisory Committee on Clinical Excellence Awards 17 ) regarding the accessibility of the scheme to all potential beneficiaries, mostly notably to women, to those working less than full time, and to senior doctors from ethnic minority backgrounds. The focus of this research was to inform the development of new scoring arrangements that are robust and equitable.…”
Section: Discussionmentioning
confidence: 99%
“…It has been criticised as being elitist, and questions have been asked regarding the scheme's value for money. 14 , 15 Specific concerns have been raised 16 (and acknowledged by the Advisory Committee on Clinical Excellence Awards 17 ) regarding the accessibility of the scheme to all potential beneficiaries, mostly notably to women, to those working less than full time, and to senior doctors from ethnic minority backgrounds. The focus of this research was to inform the development of new scoring arrangements that are robust and equitable.…”
Section: Discussionmentioning
confidence: 99%
“…Commentators have questioned the scheme from a health economics perspective, including the underlying incentive structure and more recently a study used theoretical frameworks to explore the intrinsic and extrinsic motivations of the medical profession in relation to CEAs. [6][7][8] Furthermore, concerns have been raised regarding the lack of evidence as to whether the scheme incentivises team performance or benefits patient outcomes, and that inequities lie in the allocation of awards by gender, ethnicity and medical specialty. 6 In relation to the assessment processes, earlier analysis of historical data showed that the arrangements for assessing applications were defensible, depending on the level of reliability judged to be required in the assessment process.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Despite its prominence, longevity and associated use of public funds, there has been relatively little research into the scheme. Commentators have questioned the scheme from a health economics perspective, including the underlying incentive structure and more recently a study used theoretical frameworks to explore the intrinsic and extrinsic motivations of the medical profession in relation to CEAs 6–8. Furthermore, concerns have been raised regarding the lack of evidence as to whether the scheme incentivises team performance or benefits patient outcomes, and that inequities lie in the allocation of awards by gender, ethnicity and medical specialty 6…”
Section: Introductionmentioning
confidence: 99%
“…7 The disparity was 24.5% for local awards, which went down to 5.4% for national awards. Given these disparities, criticism has also been raised about the nature of the application process, namely the dubiety of subjective scoring by panels (giving the appearance of objectivity), committees made up of (in theory) 50% medical professionals (reform in the 2000s increased lay and managerial representation), 8 the fact that CEAs far exceed other pay for performance schemes (which are generally <5% of an individual’s salary) 9 and how excellence is measured, among the other domains against which applicants are assessed. 8 , 10 A further criticism is that this scheme rewards individuals working in what is an increasingly team-focused environment in today’s NHS.…”
mentioning
confidence: 99%
“…Furthermore, the fact that CEAs were awarded for ‘excellence’ becomes increasingly harder to justify given the fact that >61% consultants received a local or national award. 8 The change of focus to ‘impact’ may be significant, but it may also be a semantic change; how this is interpreted will be critical. In saying this, it seems an opportunity was missed to more broadly scrutinise whether NCIAs could be evidence based.…”
mentioning
confidence: 99%